Correction: New knowledge on the antiglycoxidative mechanism of chlorogenic acid. Issue 7 (8th July 2015) - Fernandez-Gomez, Beatriz; Ullate, Monica; Picariello, Gianluca; Ferranti, Pasquale; Dolores Mesa, Maria; Dolores del Castillo, Maria
<x xml:space="preserve">Abstract</x> Correction for 'New knowledge on the antiglycoxidative mechanism of chlorogenic acid' by Beatriz Fernandez-Gomez et al., Food Funct., 2015, DOI: 10.1039/c5fo00194c.